ELEMENTY WIDOWISKA BOŻONARODZENIOWEGO W POEMACIE DWUNASTU ALEKSANDRA BŁOKA - Gasparow, Borys; Muszyńska, Małogrzata (Colloquia Litteraria, 2019)
“Elements of Christmas Pageant in Alexander Blok’s «The Twelve»” This paper is a an attempt of a new interpretation of Alexander Blok’s “The Twelve” in the context of Carnival customs in Russia at the end of the nineteenth century.